KETERKAITAN NILAI-NILAI ADAT UPAH-UPAH TONDI DENGAN BIMBINGAN KONSELING ISLAM PADA ETNIS BATAK MANDAILING - Laina Sari; Muaz Tanjung (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
Adat is an idea in which there are values. Each community usually has customs that can reflect the soul and personality of the community. One of them is the people of Kuala Bangka Village who have upah-upah tondi. Upah-upah tondi are ceremonies whose purpose is to restore the spirit of individuals who feel threatened by their lives. This study aims to examine the customs of upah-upah tondi. This research uses descriptive qualitative research methods with interviews, observations, documentation and literature studies as data collectors. Upah-upah tondi are considered to have a relationship with Islamic counseling guidance because in the upah-upah tondi there is a value of advice or guidance, social value, spiritual value and there is the same meaning of aqidah as counseling guidance. However, there is a difference where guiding in the custom of upah-upah tondi is carried out by the family or community. While in counseling guidance, guidance is given by an expert to the individual and can be done in the short term or long term called follow-up